Amazonian birds in more dynamic habitats have less population genetic structure and higher gene flow. Issue 9 (6th March 2023) - Johnson, Oscar; Ribas, Camila C.; Aleixo, Alexandre; Naka, Luciano N.; Harvey, Michael G.; Brumfield, Robb T.
Abstract: Understanding the factors that govern variation in genetic structure across species is key to the study of speciation and population genetics. Genetic structure has been linked to several aspects of life history, such as foraging strategy, habitat association, migration distance, and dispersal ability, all of which might influence dispersal and gene flow. Comparative studies of population genetic data from species with differing life histories provide opportunities to tease apart the role of dispersal in shaping gene flow and population genetic structure. Here, we examine population genetic data from sets of bird species specialized on a series of Amazonian habitat types hypothesized to filter for species with dramatically different dispersal abilities: stable upland forest, dynamic floodplain forest, and highly dynamic riverine islands. Using genome‐wide markers, we show that habitat type has a significant effect on population genetic structure, with species in upland forest, floodplain forest, and riverine islands exhibiting progressively lower levels of structure. Although morphological traits used as proxies for individual‐level dispersal ability did not explain this pattern, population genetic measures of gene flow are elevated in species from more dynamic riverine habitats. Our results suggest that the habitat in which a species occurs drives the degree of population genetic structuring via its impact on long‐term fluctuations in levels of gene flow, with species in highly dynamic habitats having particularly elevated gene flow. These differences in genetic variation across taxa specialized in distinct habitats may lead to disparate responses to environmental change or habitat‐specific diversification dynamics over evolutionary time scales. Resumo: A compreensão dos fatores que governam a variação da estrutura genética entre as espécies é fundamental para o estudo da especiação e da genética das populações. A estrutura genética tem sido ligada a vários aspectos da história da vida, tais como estratégia de forrageio, associação ao habitat, distância de migração e capacidade de dispersão, os quais poderiam influenciar a dispersão e o fluxo gênico. Estudos comparativos usando espécies que diferem nas suas histórias de vida oferecem uma oportunidade para desvendar o papel da dispersão no estabelecimento do fluxo gênico e da estrutura genética da população. Aqui examinamos dados genéticos populacionais de diversas espécies de aves com diferentes capacidades de dispersão especializadas em três habitats amazônicos, incluindo florestas de terra‐firme, florestas de várzea e ilhas fluviais, cujos ambientes ripários são altamente dinâmicos. Utilizando dados genô micos que incluem milhares de loci, mostramos que o tipo de habitat tem um efeito significativo na estruturação genética das populações; espécies de florestas de terra‐firme, florestas de várzea e ilhas fluviais exibem níveis de estruturação progressivamente menores. Embora os traços morfológicos frequentemente usados como indicadores da capacidade de dispersão a nível individual não expliquem este padrão, as medidas genéticas populacionais de fluxo gênico são altas em espécies associadas a habitats ribeirinhos mais dinâmicos. Nossos resultados sugerem que o habitat no qual uma espécie é encontrada determina o grau de estruturação genética da população através de seu impacto nas flutuações de longo prazo do fluxo gênico, com espécies em habitats altamente dinâmicos tendo um fluxo gênico particularmente alto. As diferenças na variação genética dos táxons especializados em diferentes habitats podem resultar em respostas díspares às mesmas mudanças ambientais, ou dinâmicas de diversificação específicas a um determinado habitat ao longo de escalas de tempo evolutivas. RESUMEN: Comprender los factores que rigen la variación de la estructura genética entre especies es clave para el estudio de la especiación y la genética de poblaciones. La estructura genética se ha relacionado con varios aspectos de la historia vital, como la estrategia de búsqueda de alimento, la asociación de hábitats, la distancia de migración y la capacidad de dispersión, factores todos ellos que podrían influir en la dispersión y el flujo genético. Los estudios comparativos de datos genéticos poblacionales de especies con historias vitales diferentes ofrecen la oportunidad de desentrañar el papel de la dispersión en la conformación del flujo genético y la estructura genética poblacional. En este trabajo examinamos los datos genéticos de poblaciones de especies de aves especializadas en una serie de hábitats amazónicos que, según la hipótesis, filtran especies con capacidades de dispersión radicalmente diferentes: bosques estables de tierras altas, bosques dinámicos de llanuras aluviales e islas fluviales altamente dinámicas. Utilizando marcadores genómicos, demostramos que el tipo de hábitat tiene un efecto significativo en la estructura genética de la población, y que las especies de los bosques de tierras altas, los bosques inundables y las islas fluviales presentan niveles de estructura progresivamente más bajos. Aunque los rasgos morfológicos utilizados como indicadores de la capacidad de dispersión individual no explican este patrón, las medidas genéticas poblacionales del flujo genético son más elevadas en las especies de há bitats fluviales más dinámicos. Nuestros resultados sugieren que el hábitat en el que se encuentra una especie determina el grado de estructuración genética de la población a través de su impacto en las fluctuaciones a largo plazo de los niveles de flujo genético, siendo las especies de hábitats muy dinámicos las que presentan un flujo genético particularmente elevado. Estas diferencias en la variación genética entre taxones especializados en hábitats distintos pueden dar lugar a respuestas dispares al cambio ambiental o a dinámicas de diversificación específicas del hbitat a lo largo de escalas temporales evolutivas.